Training the 21st century police officer : redefining police professionalism for the Los Angeles Police Department - Glenn, Russell W. (RAND, 2003)
This book summarizes a study conducted by RAND for the Los Angeles Police Department (LAPD). The object of this book is to provide analyses and recommendations to assist the LAPD in meeting certain requirements and ultimately enabling LAPD to better serve the interests of the people of Los Angeles through improved training in five critical areas: use of force, search and seizure, arrest procedures, community policing, and diversity awareness.